2012
DOI: 10.1002/cm.21000
|View full text |Cite
|
Sign up to set email alerts
|

The structural heterogeneity of radial spokes in cilia and flagella is conserved

Abstract: Radial spokes are ubiquitous components of motile cilia and flagella and play an essential role in transmitting signals that regulate the activity of the dynein motors, and thus ciliary and flagellar motility. In some organisms the 96 nm axonemal repeat unit contains only a pair of two spokes, RS1 and RS2, while most organisms have spoke triplets with an additional spoke RS3. The spoke pair in Chlamydomonas flagella has been well characterized, while spoke triplets have received less attention. Here, we used c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(118 citation statements)
references
References 71 publications
(148 reference statements)
10
107
1
Order By: Relevance
“…RTDR1, PPIL6, and NME5 were present at lower abundance. While several elegant studies (e.g., 14, 57, 58) have begun to determine the detailed molecular structure and composition of the radial spokes in other species, little is known about the relative abundance of individual radial spoke proteins in human cilia. Comparing the predicted stoichiometry of these proteins with those from a published model of a C. reinhardtii radial spoke (57) (Table 3) shows a similar pattern of abundance, with the spoke head proteins generally more abundant than those of the stalk or neck.…”
Section: Resultsmentioning
confidence: 99%
“…RTDR1, PPIL6, and NME5 were present at lower abundance. While several elegant studies (e.g., 14, 57, 58) have begun to determine the detailed molecular structure and composition of the radial spokes in other species, little is known about the relative abundance of individual radial spoke proteins in human cilia. Comparing the predicted stoichiometry of these proteins with those from a published model of a C. reinhardtii radial spoke (57) (Table 3) shows a similar pattern of abundance, with the spoke head proteins generally more abundant than those of the stalk or neck.…”
Section: Resultsmentioning
confidence: 99%
“…Recent cryoET studies have demonstrated that while radial spoke 1 and 2 in Chlamydomonas are very similar, the third radial spoke in Tetrahymena and Strongylocentrotus is unique (Barber et al 2012; Lin et al 2012; Pigino et al 2011). The human average also shows that the third radial spoke is different in shape with a wider spoke head and a faint diagonal linker compared with spokes 1 and 2 (Figures 4B, D).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 50 original CMF genes identified in T. brucei (19), 5 have now been demonstrated or implicated to function as part of the NDRC: trypanin, CMF70, CMF46, and CMF44 (22,23,25,26,64) and, as discussed above, CMF22. While CMF proteins themselves are broadly conserved, they interact with conserved as well as organism-specific proteins (94,95). Continued analysis of CMF22 and other CMF proteins therefore offers opportunities to enhance understanding of flagellum motility with relevance to the pathogenesis of trypanosomes and related human pathogens.…”
Section: Discussionmentioning
confidence: 99%